Child Development Policy in Thailand: A Case Study of Successful Daycare Center - Congkrarian, Ekaphot (Journal of Dhamma for Life, 2023)
This qualitative documentary research delves into the intricacies and aim to study of the child development policy in Thailand: A case study of successful daycare center. Through key informant interviews, the study unfolds the multifaceted approach adopted at various policy levels to foster the comprehensive development of young children. The results of the research unveil a three-tiered policy framework. At Level 1, the "National Strategy 2018-2037" prioritizes the development and fortification of human resources across the lifespan. Level 2, operating under the national strategy, concentrates on enhancing human potential from pregnancy to old age. Specifically, the policies address the holistic development of early childhood, encompassing physical, emotional, social, intellectual, linguistic, ethical, and social communication aspects. Furthermore, Level 3 introduces the "Reproductive Health Development Policy and Strategy 2017-2026," which emphasizes quality birth and growth. This entails proactive planning before conception, support for conception, and ensuring a nurturing environment for children’s growth and development. The research underscores the significance of systematic planning and organization in daycare center management. This involves meticulous work planning, appointment of qualified personnel, role-based control and coordination, and transparent budgeting. The adherence to these practices ensures the efficient functioning of the daycare center and serves as a blueprint for other centers aiming to achieve similar success. Crucially, the findings emphasize the need for adaptability within the daycare center management model to align with diverse contexts, including private sector agencies, government entities, and the unique characteristics of Bangkok. This research contributes to the broader understanding of effective child development policies and offers insights for the advancement of daycare centers seeking both efficiency and effectiveness.